Evaluation of a Cryptococcus capsular polysaccharide detection FungiXpert LFA (lateral flow assay) for the rapid diagnosis of Cryptococcosis. (1st April 2022) - Liu, Ya; Kang, Mei; Wu, Si-Ying; Wu, Li-Juan; He, Lan; Xiao, Yu-Ling; Zhang, Wei-Li; Liao, Quan-Feng; Deng, Jin; Chen, Zhi-Xing; Ma, Ying
Abstract: Cryptococcus is an opportunistic pathogenic fungus and is the major cause of fungal meningitis. The cryptococcal antigen (CrAg) lateral flow assay (LFA) is an immunochromatographic test system that has simplified diagnosis as a point-of-care test. In this study, we evaluated the diagnostic performance of Cryptococcal capsular polysaccharide detection FungiXpert (Genobio Pharmaceutical, Tianjin, China) using serum and cerebrospinal fluid (CSF) samples for the diagnosis of cryptococcosis and investigated the cross-reaction of the assays to pathogenic fungi and bacterium by comparing it to the U.S. Food and Drug Administration (US FDA)-approved IMMY CrAg LFA. Eighty CSF and 119 serum/plasma samples from 158 patients were retrospectively collected to test for qualitative or semi-quantitative detection of CrAg. Cross-reaction of the assays was tested using 28 fungi and 1 bacterium. Compared to IMMY CrAg LFA, the FungiXpert LFA demonstrated 99.1% sensitivity and 98.9% specificity in the qualitative test. In the 96 semi-quantitative CrAg assay results, 39 (40.6%) test titers of FungiXpert LFA were 1–2 dilutions higher than those of IMMY CrAg LFA. The Intraclass Correlation Coefficient of the Semi-quantitative results of CrAg titer tests via the two assays was 0.976. Similar to IMMY CrAg LFA, FungiXpert LFA showed cross-reactivity with Trichosporon asahii . Compared with the IMMY CrAg LFA, the FungiXpert LFA showed an equal, yet, excellent performance. However, it is important to note that these two assays have potential cross-reactivity to T. asahii when diagnosing patients. FungiXpert LFA is a rapid screening method for the effective and practical diagnosis and treatment of cryptococcosis. Lay summary: The FungiXpert LFA was developed to diagnose fungal meningitis caused by Cryptococcus yeasts, by using serum or cerebrospinal fluid. It was compared to an existing lateral flow assay (LFA). The FungiXpert LFA performed well in qualitative and semi-quantitative tests.